Adapting Islamic Education to Modern Realities: Trends and Challenges in 2024 - Elihami Elihami; Sukman S; Sing Sicat (Edumaspul: Jurnal Pendidikan, 2024)
The landscape of Islamic education is undergoing significant transformations in response to the evolving demands of the modern world. This study delves into the trends and challenges facing Islamic education in 2024, focusing on the imperative of adapting traditional teachings to contemporary realities. Through a comprehensive analysis of current practices and emerging trends, this research seeks to elucidate the strategies employed by educational institutions to navigate the complexities of globalization, technology integration, and socio-cultural shifts while preserving the core tenets of Islamic pedagogy. Key themes explored include the integration of digital learning platforms, the cultivation of critical thinking skills within an Islamic framework, and the promotion of religious tolerance and interfaith dialogue. Additionally, the study examines efforts to enhance educational accessibility and inclusivity, particularly for marginalized groups such as women and minorities. Furthermore, this research investigates the role of Islamic education in fostering social cohesion, ethical leadership, and sustainable development in the face of contemporary challenges. By highlighting innovative approaches and best practices, this study aims to provide valuable insights for educators, policymakers, and stakeholders invested in the advancement of Islamic education in the twenty-first century. Ultimately, the findings of this research contribute to the ongoing dialogue on the harmonization of tradition and modernity in Islamic pedagogy, with implications for fostering a more inclusive, dynamic, and relevant educational paradigm.